Peran Koperasi Syariah Dalam Meningkatkan Perekonomian Masyarakat Desa Harapan Makmur - Dwi Siyamsih (Journal of Islamic Economy, 2024)
The purpose of writing this research is to find out the role of Sharia Cooperatives in improving the economy of Harapan Makmur Village Community. This type of research is qualitative research. Research reveals phenomena or events by explaining, describing / describing in clear and detailed words through language that is not aimed at numbers / numbers. Qualitative research is research that solves problems using empirical data. This research technique uses inductive techniques based on specific facts, then analyzed and finally found a general problem solving. The result of the research is that the existence of a Sharia Cooperative in Harapan Makmur Village is very helpful as a solution to the wheels of the community economy. With this Sharia Cooperative, the income of members of the Harapan Makmur Village Sharia Cooperative has increased. Harapan Makmur Village Sharia Cooperative has a positive influence on Cooperative members, because in addition to being a capital provider, Sharia Cooperatives also make people avoid practices that are prohibited in Islam such as Maysir, Gharar, and Riba.